Short- and long-glass fibre reinforced polyamide 6,6 composites: Fibre length characteristics of injection moulded specimens - Hassan, Aziz; Yahya, Rosiyah; P. R, Hornsbry, (Malaysian Journal of Science, 2001)
Injection moulding of the dry blend of fibre and polymer matrix usually results in composite materials with poor physical properties. Therefore, the processing of fibre reinforced composite materials usually involved compounding and moulding. These processes, however, are associated with the problem of fibre breakage. In this work, short and long glass fibre reinforced polyamide 6,6 composites, prepared by extrusion and pultrusion compounding respectively, were injection moulded. Test pieces were then subjected to fibre length distribution characterisation. lt was found that pultrusion compounded composites showed superior fibre characteristics compared to the extrusion compounded composites counterpart. These fibre length characteristics were also in agreement with the improved tensile strength and tensile modulus of` long fibre composites over the short fibre composites.